Efficient fast electron generation in an interaction of Intense, ultrashort laser with metal nanoparticle coated dielectric target. (May 2016) - Sarkar, Deep; Tata, Sheroy; Shaikh, Moniruzzaman; Lad, Amit D.; Adak, Amitava; Sarkar, Subhrangsu; Ayyub, Pushan; Kumar, G. Ravindra
Abstract: Hot electron generation in intense laser-matter interaction studies is a topic of great interest due in significant part to its applications in fast ignitor scheme in Inertial Confinement Fusion (ICF). We measure the hot electron energy spectrum from Ag nanoparticle coated fused silica target (100 μm thick) interacting with an intense (I∼10 18 W/cm 2 ), short pulse (τ∼ 30× 10 -15 s) laser and compare the results with those of an uncoated fused silica. Enhancement in hot electron energy and hard x-ray yield is measured as a function of thickness of Ag nano-coating, varied from tens of nm to hundreds of nm. The hot electron temperatures and integrated x-ray yield are observed to be greater for subwavelength film thicknesses for the case of a p-polarized laser. Such results indicate that metal nanoparticle layers have an important role to play in the enhancement of laser-plasma coupling efficiency for short scale-length plasmas created in femtosecond laser interactions.